2018
DOI: 10.1016/j.ibusrev.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The export performance of emerging economy firms: The influence of firm capabilities and institutional environments

Abstract: We advance a two-stage theoretical model which contends that the export performance of emerging economy firms (EEFs) will depend both upon their firm-specific capabilities and their home institutional environments. Specifically, we argue that EEFs will be more likely to export when facing more uncertainty at home from greater political instability, substantial informal competition, and high corruption. Furthermore, we hypothesize that firmsÕ export intensities will be contingent upon specialized internal capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(189 citation statements)
references
References 120 publications
12
169
3
5
Order By: Relevance
“…SMEs have limited resources for trial and error; understanding the impact of digitalization is necessary for their results-based decision making. Firms under the pressure of competition due to market transparency and liberalization tend to expand their market for growth and survival (Krammer et al, 2017;Wilden, Gudergan, & Nielsen, 2013).…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…SMEs have limited resources for trial and error; understanding the impact of digitalization is necessary for their results-based decision making. Firms under the pressure of competition due to market transparency and liberalization tend to expand their market for growth and survival (Krammer et al, 2017;Wilden, Gudergan, & Nielsen, 2013).…”
Section: Model Developmentmentioning
confidence: 99%
“…Strong relationships with government as part of the network also enable SMEs to gain benefits from government support programmes (Faroque & Takahashi, 2015). Krammer, Strange, and Lashitew (2017) found that access to external technology via licensing is one kind of relational resource that positively related to the export intensity of these firms. Many studies have found a positive relationship between network and firm performance (Kim & Hemmert, 2016;Krammer et al, 2017;Zhou et al, 2007).…”
Section: Networkmentioning
confidence: 99%
“…There is no consensus among the scholars on the meaning of firm capability as several scholars perceive the concept differently. Krammer et al (2018) view firm capability as actions, processes, and systems and associations' businesses may undertake using it available resources. As such, Barney and Arikan (2001) assert that firm capability includes factors that enhance small business' awareness of strategic prospects/threat and its ability to undertake strategies.…”
Section: Firm Capability and Business Performancementioning
confidence: 99%
“…Krammer advances a two-stage theoretical model which contends that the export performance of emerging economy firms (EEFs) will depend both upon their firm-specific capabilities and their home institutional environments. Specifically, they argue that EEFs will be more likely to export when facing more uncertainty at home from greater political instability, substantial informal competition, and high corruption (Krammer et al, 2018).…”
Section: Recent Research and Publications Analysismentioning
confidence: 99%